Analysis of structural and organisational arrangements of monitoring and evaluation status for the public sector in Zambia - Kanyamuna, Vincent (Advances in Social Sciences Research Journal, 2020)
This study was an exploratory investigation of the prevailing status of Zambia’s public sector monitoring and evaluation (M&E) structural and organisational arrangements. As a good governance and accountability instrument, a country’s whole-of-government monitoring and evaluation system (WoGM&ES) is supposed to be functionally operated if it was to offer desired benefits. But how do you properly fix a government’s M&E system? Conducting a rigorous diagnostic exercise on the existing system gives a chance to know what works, what does not work and reasons why. It was the objective of this research to critically bring out elements that required attention and those that needed scaling up as well as sustaining. Using the diagnostic checklist comprised of ten (10) components and the LEADS scoring system, different statuses about M&E structural and organisational arrangements for Zambia’s government M&E system were assessed and analysed. The elements assessed include coordination and oversight; joint sector reviews; working groups; ownership; incentives; and linkage with statistical office; horizontal integration; vertical upward integration; vertical downward integration; and link with projects. The findings have shown that overall, the structural and organisational arrangements (that is, structure & linkages) are weak with a LEADS score of point 2—meaning only elements existed. Further in-depth analysis of intra-component status showed that while other elements were less developed, others were fairly well implemented. The diagnosis results are critical to the Zambian government and its stakeholders in knowing which aspects to improve in the effort to build, strengthen and sustain a stronger WoGM&ES going forward.